Medindo a intensidade da pobreza: possibilidade de operacionalização da Capability Approach por meio da metodologia Alkire-Foster - Mosaner, Marcelo Amado Sette (2016)
The Capability Approach (CA) is a normative framework initially developed by Amartya Sen in the seventies, featuring human development as the process of expansion of the range of opportunities available to and valued by individuals. Although the CA has undeniable contributions to welfare assessment - as the creation of the HDI, MPI and other indicators published by UNDP - its critics point out to the huge gap between its key concepts and the real possibilities to use this normative framework in empirical applications, primarily for evaluation issues as quality of life, poverty and inequality. Meanwhile, the field of direct multidimensional poverty measurement is one of the most prominent fields of CA operationalization. In this sense, five central challenges to CA operationalization were first identified and then related to the multidimensional poverty measurement methodology developed by Alkire and Foster (2007, 2011a), focusing on understanding - in general – which are the conditions for empirical applications based on AC framework and - in particular - to what extent the AF methodology responds to these difficulties. The challenges identified relates to the conversion of the intrinsic complexity of measuring human well-being into synthetic indicators : (1) the choice of dimensions, indicators and relative weights, (2) the contrafactual character of the problem of measurement of individual liberties, or capabilities, (3) the question of individual methodological focus or collective, (4) access to data and (5) data aggregation in multiple dimensions. It is concluded that the AF methodology is able to generate multidimensional poverty measures that are consistent with the CA framework, provided that some operational conditions described in the literature are respected. Furthermore, AF has important innovations to public policy as the measure (M0) of multidimensional poverty incidence adjusted to intensity, the adjusted multidimensional poverty gap (M1) and its squared gap (M2) that can be further disaggregated by family, individual or subgroup, making possible to identify simultaneous deprivations suffered by the same unit of analysis